Reduced-Pressure Boiling Extraction of Oleuropein Coupled with Ultrasonication from Olive Leaves (Olea europaea L.). (3rd September 2015) - Xie, Pu-jun; Huang, Li-xin; Zhang, Cai-hong; You, Feng; Wang, Cheng-zhang; Zhou, Hao
Abstract : Oleuropein was extracted from Frantoio olive leaves using reduced-pressure boiling extraction coupled with ultrasound-assist (URPE). Four important factors, extraction temperature, ultrasonic power, ethanol concentration, and the ratio of solid to liquid, were selected to carry out the response surface methodology (RSM) for seeking optimal conditions on high oleuropein extraction yield at different levels. Box-Behnken design was employed to investigate the effects of the four factors on it. The results showed that the ratio of solid to liquid was the most significant factor of all on oleuropein yield. The optimal operation conditions were obtained as follows: ethanol concentration 75% (v/v), extraction temperature 53°C, ultrasonic power 600 W, and the ratio of solid to liquid 1 : 31. Under these optimal conditions, oleuropein extraction yield was 7.08%, which was close to the predicted value 7.121%. The scanning electron microscope (SEM) images of olive leaves after extraction were provided as well. It was seen that, compared with the untreated leaves, URPE could effectively break cells within the olive leaves.